(untitled) (Journal of the College of Education for Women, 2026)
The industrial presence, especially in residential areas, has many negative and positive effects at the same time. As for the negative impact, it lies in environmental pollution therefore this study indicates the importance of industrial planning to achieve a balance between the requirements of industrial production and maintaining environmental balance, especially in residential areas. the most important theories dealing with the issue of the overlap of industrial activity with residential areas are mentioned such as the linear city theory and the modern satellite city theory. As for the positive aspect of the industrial presence especially after the use of technology which contributed to achieving part of the environmental balance. Baghdad Governorate was chosen as a study model due to its population density and industrial activity. Baghdads population is constantly increasing, resulting in the need for many products. Which consequently leads to the divesing of industries. and the increase of job opportunities, this study with the types of industries its number and the nember of workers and their wages in Baghdad Governorate. it is clear that the number of industries is constantly increasing in the governorate due to the increasing population it is also noted that there are many residential areas that are referred to as industrial due to the dense spread of industries in them, such as the Al-Waziriyah, Awerij, Al-Kamaliyah, Bob Al-sham and Jamila Industrial areas.